Artificial Intelligence System Integrated With Smartphone Application For Early Detection Of Stunting Based On Toddler Growth Index - Iskandar, Dwi; Putri, Frestiany Regina; Kusuma, Junianto Chandra; Saputro, Rizal Tommy (International Journal of Computer and Information System (IJCIS), 2024)
Toddlers have certain characteristics and needs that require growth monitoring. Toddlers will experience a period called the "Golden age" which is a period of experiencing a golden period in early life. What needs to be considered during the Golden Age of Toddlers is the record of weight, height, and head circumference of the child at each visit, then the results are recorded using the Healthy Menu Card. Collaboration between Artificial Intelligence and IoT can provide innovative and effective solutions, these two fields of science can be collaborated with IoT Sensors for measuring weight and height, data collection and storage, AI systems for data analysis, providing recommendations, notification systems and monitoring. The method used to complete this research is a literature study and data collection to find reference materials, design technology concepts, development preparation, hardware assembly, Arduino IDE coding, uploading coding to hardware, PHP (Hypertext Preprocessor) coding, uploading PHP (Hypertext Preprocessor) Code to hosting, coding .Apk (Android Package), technology trials. This application is available on two platforms, namely web-based and Android. Everyone can weigh, but to record data to the system, users must register to get an account and QR code. QR code is used to transfer weight and height data into the system, and the account allows the user to view all weighing data and history. The system also displays a graph containing height, weight, and upper and lower limits of ideal weight.